THE STATUS OF THE WIDOW AS HEIR TO THE ASSETS INHERITED FROM HER DECEASED HUSBAND IS REVIEWED ACCORDING TO CUSTOMARY LAW - Shinta Nofitrianti; Syuryani; Suryamizon, Anggun Lestari (Fakultas Hukum Universitas Djuanda, 2024)
Customary law, which is unwritten, makes customary law dynamic in nature so that it is easy to adapt to developments required by the times. Determining the ownership status of assets during marriage is important to obtain clarity on what position the assets will be in the event of the death of one of the husbands or wives, which are the inheritance to be inherited by their respective heirs. Becoming a widow can occur due to divorce or death. The problem that the author examines is how to regulate inheritance in marriage law according to customary law in Nagari Sungai Rimbang, Suliki sub-district, and how is the position of a widow regarding her husband's inherited assets who have died in Nagari Sungai Rimbang, Suliki sub-district. The research method that the writer uses is Empirical Legal Research. Therefore, it can be concluded 1) Inherited Property Arrangements in Marriage Law According to Customary Law in Nagari Sungai Rimbang, Suliki District, Inherited property is property owned by a man or woman, during bachelors or girls who were obtained through gifts, wills or from business Alone. If the property is brought into the marriage of the man or woman dies, then the inherited property is returned or returned to the family of the man or woman from the mother's line. 2) A widow does not have the right to her deceased husband's property. The widow gets the right to hereditary property if before her husband dies he has given a will to the bequeathed person. If the widow has children, both girls and boys, from a legal marriage with the husband, then the child gets a share by way of both parties conducting deliberation.